A Hybrid Model as a Decision Support System in Internet Service Providers (ISP) Selection for hotels - I Wayan Surya Pramana; Gede Wirya Wardhana (Jurnal Krisnadana, 2025)
Reliable internet connectivity has become a critical requirement in the hospitality industry because it directly impacts to service quality and guest satisfaction. Hotels must carefully select an Internet Service Provider (ISP); however, this decision is often complicated by the wide choice of providers, budget constraints, and vary in guest internet needs. A survey to hotel IT practitioners in Bali highlighted the challenges in ISP selection, where mistakes can decrease customer satisfaction and damage a hotel's reputation. To address this, this study proposes a hybrid decision support system model that integrates the Naïve Bayes algorithm with the Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW). Naïve Bayes is used for the classification process, while AHP and SAW are used for the ranking process. Based on the implementation and analysis results, it was found that this model achieved an accuracy of 65%. Furthermore, it was also found that the accuracy of this model was greatly influenced by the results of the classification process.